(untitled) (International Journal of Engineering and Computer Science, 2016)
This paper presents the Image Enhancement using Contrast Limited Adaptive Histogram Equalization method and Wiener filter to remove the noise that might be presented in image. Gamma correction technique is used to transfer the image in to a suitable dynamic range. To avoid amplifying any noise that might be present in an image we use contrast limited adaptive histogram equalization parameter to limit the contrast especially in homogeneous area.